2017
DOI: 10.1080/03091902.2017.1364308
|View full text |Cite
|
Sign up to set email alerts
|

A novel obstetric medical device designed for autotransfusion of blood in life threatening postpartum haemorrhage

Abstract: Postpartum haemorrhage (PPH) is an obstetric emergency caused by excessive blood loss after delivery, which is the leading cause of maternal mortality worldwide. PPH can lead to volume depletion, hypovolemic shock, anaemia and ultimately death. The prevalence of PPH is disproportionately higher in low resource settings where there is limited access to skilled medical care and safe blood supplies. Current management strategies target both prevention and treatment of PPH however no alternatives currently exist t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The included studies were also classified according to the allocation concealment defined by the Cochrane Selection bias 1 Performance bias 2 Viés de detecção 3 Detection bias 4 Reporting bias 5 ? ?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were also classified according to the allocation concealment defined by the Cochrane Selection bias 1 Performance bias 2 Viés de detecção 3 Detection bias 4 Reporting bias 5 ? ?…”
Section: Resultsmentioning
confidence: 99%
“…Postpartum hemorrhage is defined as an obstetric emergency caused by excessive and/or cumulative blood loss (greater than 1,000 mL) within 24 hours (primary or early) or after this period (secondary) due to uterine atony or failure of the uterus to contract and retract after the child is born, regardless of the mode of delivery, resulting in signs and symptoms of hypovolemia and hemorrhagic shock. [1][2][3][4] This condition is one of the most common complications in clinical obstetric practice, notably in its most severe form (hemorrhage > 1,500 mL), accounting for about 30% of maternal deaths. It requires immediate recognition and management to avoid significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis on AT was assessed and sorted as: main theme (8 records), [28][29][30][31][32][33][34][35] section (6 records) 18 36-40 or mentioned (24 records) (online supplemental file 4).…”
Section: Outline Of Records Includedmentioning
confidence: 99%
“…Only one journal article specifically studied the clinical use of AT in an LRS. 29 The remaining research articles either reported on the development of an AT device for use in an LRS [30][31][32][33][34] or did not have AT as their main theme. 36-38 41-47 AT in LRS continues to be thought of, reported as, or portrayed as a safe 26 28 29 41 and life-saving technique.…”
Section: Outline Of Records Includedmentioning
confidence: 99%
“…IAT is another technology that can provide life-saving blood in emergent situations no available blood. 5 Handheld, portable, and reusable IAT devices have recently been designed for low-resource environments without a stable blood supply. 5 This process aids in stabilizing patients until definitive treatment can be administered, necessitating proper training for healthcare providers to implement this technique in the delivery room.…”
mentioning
confidence: 99%